1998
DOI: 10.1515/hfsg.1998.52.6.582
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Quantitative Determination of K and Ca in Phloem, Cambium, and Xylem Cells of Spruce(Picea abies[L.] Karst.) During Earlywood and Latewood Formation

Abstract: The present investigation was directed to calibrated subcellular quantitative determination of K and Ca in phloem, cambium, and xylem cells of spruce (Picea abies [L] Karst.) by energy dispersive X-ray spectroscopy (EDXS) in combination with transmission electron microscopy (TEM). The element content was studied during earlywood and latewood formation throughout primary and secondary wall formation and lignification. In the experimental stage, increment cores were extracted from three 100-year-old forest tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
0
15
0
2
Order By: Relevance
“…K also influences xylem structure, probably through its role in turgor‐driven elongation of new xylem cells. It has an impact on the deposition dynamics of SCWs as K‐starved trees show earlier initiation of SCW deposition than controls (Dunisch et al ., ; Langer et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…K also influences xylem structure, probably through its role in turgor‐driven elongation of new xylem cells. It has an impact on the deposition dynamics of SCWs as K‐starved trees show earlier initiation of SCW deposition than controls (Dunisch et al ., ; Langer et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Arens (1958a, b) attributed the scleromorphic traits of cerrado plant species to the mineral deficiency, particularly N, P, Ca and S, which would limit plant growth, provide accumulation of carbohydrates, and deposit in the wall of plant cell, as cellulose, sclerenchyma and other mechanical structures. Also, some authors (Eklund and Eliasson 1990;Dunisch et al 1998) found that the reduction of the thickness of the cellular wall in some plants is influenced by potassium, which in high concentration decrease calcium absorption. These authors observed an increased of synthesis of cellular wall, and higher lignification with increasing concentration of calcium.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed that potassium homeostasis in trees depends on the availability of mineral nutrients, the state of mycorrhizal association as well as the physiological condition of the plant. During cambial growth K + ions have been shown to be involved in various aspects of xylogenesis (Du¨nisch and Bauch 1994a, b;Kuhn et al 1997), such as cell expansion via increase of the symplastic K + content (Du¨nisch et al 1998) and xylem differentiation . Furthermore K + fertilisation resulted in a 30% increased biomass and enlarged annual rings as a result of the potassium peak in the cambial region during the active growth period of trees (Kuhn et al 1997;Arend et al 2002).…”
Section: Introductionmentioning
confidence: 99%